Mental health and fatigue status of the medical workforce during the COVID-19 outbreak in the Yangzhou city, China - Tang, Xiaojia; Pei, Yunlong; Wang, Xin; Jiang, Li; Liu, Peipei; Chen, Yingzhu; Meng, Zhaoxiang (Frontiers in Psychiatry, 2022)
Background When the coronavirus disease 2019 (COVID-19) erupted in Yangzhou, China, at the end of July 2021, medical workers in Yangzhou immediately joined the frontline for the fight against the pandemic. This study aimed to identify the mental health and fatigue experienced by the medical workers in Yangzhou during the COVID-19 outbreak. Methods We included 233 medical workers who participated in the front-line work for more than 1 month through the questionnaire, including doctors, nurses, medical technicians and medical students. The generalized anxiety disorder-7 (GAD-7), patient health questionnaire-9 (PHQ-9), and Fatigue self-assessment scale (FSAS) were administered to the participants and their responses were evaluated. Results A total of 233 eligible questionnaires were received. Among them, 130 people (57.08%) were probably anxious and 141 (60.52%) people were clinically depressed. Poor sleep was considered an independent risk factor for anxiety (OR = 7.164, 95% CI: 3.365 15.251, p = 0.000) and depression (OR = 6.899, 95% CI: 3.392 14.030, p = 0.000). A high PHQ-9 score was considered an independent risk factor for general fatigue (OR = 1.697, 95% CI: 1.481 1.944, p = 0.000). Mental fatigue (OR = 1.092, 95% CI: 1.027 1.161, p = 0.005) and fatigue response to sleep/rest (OR = 1.043, 95% CI: 1.011 1.076 p = 0.008) were considered independent risk factors for general fatigue. Conclusion Poor quality of sleep led to probable anxiety, depression, and general fatigue. Mental fatigue and fatigue response to sleep/rest were independent risk factors for depression, which merits attention for battling COVID-19.